АДМИНИСТРАТИВНО-ПРАВОВЫЕ ФОРМЫ И МЕТОДЫ ПРОТИВОДЕЙСТВИЯ ПРОСТУПКАМ В СФЕРЕ ОБЕСПЕЧЕНИЯ БЕЗОПАСНОСТИ ДОРОЖНОГО ДВИЖЕНИЯ - Солонецкий, Иван Иванович (SUPREMANCE OF LAW, 2016)
The main methods of administrative and legal counteraction to misdemeanors in the field of road safety are investigated, a characteristic of their content, features of application and interaction are given. The content of the concepts "form of administrative and legal counteraction", "method of administrative and legal counteraction" is determined; ) and methods of countering misdemeanors in the field of road safety (persuasion, encouragement and coercion in the form of measures of administrative prevention, administrative suppression and administrative penalties).
Keywords: traffic safety; misconduct; counteraction; forms; methods; prevention; control and supervision; legal education; administrative responsibility; administrative conviction; administrative coercion.